Prevention of Stunting among Pregnant Women through Mindfulness Training and Health Education in Solok District - Yarmis Syukur; Ade Herdian Putra; Triave Nuzila Zahri; Azmatul Khairiah Sari (Jurnal Aplikasi IPTEK Indonesia, 2024)
This Community Service (PkM) activity aims to reduce the birth rate of stunted babies in Nagari Kinari, Bukit Sundi District, Solok Regency, through mindfulness training and health education for pregnant women. Stunting is a serious health problem affecting children's physical and cognitive development. One of the main causes of stunting is stress in pregnant women, which impacts fetal development. Mindfulness training was introduced to help pregnant women manage stress, thus creating a healthier environment for fetal growth. This activity was carried out for two days on August 3-4, 2024, in Nagari Kinari, involving 30 pregnant women as participants. The program included health counseling, mindfulness practice sessions, discussions, and consultations with health workers. The program results showed a significant decrease in participants' stress levels and increased knowledge about pregnancy health and the importance of stress management. The mindfulness therapy taught proved effective and can be applied by the participants in their daily lives. In conclusion, this training contributes to efforts to prevent the birth of stunted babies. It is expected to be a model intervention applied in other areas with similar problems.